NFV-Based Scalable Guaranteed-Bandwidth Multicast Service for Software Defined ISP Networks - Soni, Hardik; Dabbous, Walid; Turletti, Thierry; Asaeda, Hitoshi (IEEE Transactions on Network and Service Management, 2017)
New applications where anyone can broadcast high quality video are becoming very popular. Internet services providers (ISPs) may take the opportunity to propose new high quality multicast services to their clients. Because of its centralized control plane, software defined networking (SDN) enables the deployment of such a service in a flexible and bandwidth-efficient way. But deploying large-scale multicast services on SDN requires smart group membership management and a bandwidth reservation mechanism with QoS guarantees that should neither waste bandwidth nor impact too severely best effort traffic. In this paper, we propose: 1) a scalable multicast group management mechanism based on a network function virtualization approach for software defined ISP networks to implement and deploy multicast services on the network edge and 2) the lazy load balancing multicast (L2BM) routing algorithm for sharing the core network capacity in a friendly way between guaranteed-bandwidth multicast traffic and best-effort traffic and that does not require costly real-time monitoring of link utilization. We have implemented the mechanism and algorithm, and evaluated them both in a simulator and a testbed. In the testbed, we experimented the group management at the edge and L2BM in the core with an open vSwitch-based QoS framework and evaluated the performance of L2BM with an exhaustive set of experiments on various realistic scenarios. The results show that L2BM outperforms other state-of-the art algorithms by being less aggressive with best-effort traffic and accepting about 5%-15% more guaranteed-bandwidth multicast join requests.